Obstetricians' knowledge of periodontal disease as a potential risk factor for preterm delivery and low birth weight - José Mariano da Rocha; Vanessa Rodrigues Chaves; Almir Antônio Urbanetz; Renata dos Santos Baldissera; Cassiano Kuchenbecker Rösing (Sociedade Brasileira de Pesquisa Odontológica, 2011)
There is little information about the knowledge and attitudes of physicians regarding oral care. This study aimed to assess the knowledge and attitudes of obstetricians about the relationship between periodontal disease and preterm/low birth weight. A questionnaire was emailed to members of the Brazilian Federation of Gynecology and Obstetrics (FEBRASGO). The questionnaire elicited both personal information and knowledge and attitudes regarding the relationship between periodontal diseases and preterm labor. A total of 875 obstetricians responded to the questionnaire. The majority of respondents were female (54.1%), resided in the Southeast (45.6%), worked in both the public and private sectors (61.4%), and had over 15 years of experience in obstetrics (48.9%). A large proportion of obstetricians (93.4%) stated that bacteria were associated with periodontal disease, and 94% reported that periodontitis was a condition more severe than gingivitis. In total, over 80% of participating obstetricians reported smoking, preeclampsia, bacterial vaginosis and periodontal disease as risk factors or possible risk factors for preterm birth or low birth weight. A correlation between the experience of the obstetricians and referral of their patients for dental examinations (p < 0.001) was observed. Also, obstetricians who had had their own dental visits more recently were more likely to recommend the same for their patients (p < 0.001). It is concluded that, although obstetricians were aware of the association between gingival inflammation and adverse obstetric outcomes, the attitudes of these professionals were not in agreement with their apparent knowledge regarding periodontal diseases and their possible repercussions.